Ketakberdayaan Mempertahankan Persediaan dan Modal Akibat Covid_19: Studi Kasus Gadde-gadde Mama Robi - Andi Sri Wahyuni; Rezky Salsabila Sitanggang (JOURNAL OF EDUCATIONAL TECHNOLOGY, CURRICULUM, LEARNING AND COMMUNICATION, 2021)
The outbreak of the Covid_19 pandemic in Indonesia, which reached its climax in May 2021, caused the government to issue a restriction policy which resulted in the closure of Mama Robi's business. This study aims to understand the process that occurred in Mama Robi's gadde-gadde, from being able to last for fourteen years to being collapsed during a pandemic. By using a qualitative approach, this study was designed with a case study method. Triangulation techniques were carried out during data collection and analysis to test and strengthen the validity of existing data. The results of the analyzed data showed that the restriction caused Mama Robi to lose her customers. In addition, the restriction caused Mama Robi and her family to take their own supplies at her gadde-gadde stall, which drained Mama Robi's sales of gadgets. Mama Robi's initial capital ran out and the gadde-gadde was closed. The results of this study can be used as a basis for the government to make policies that are friendly to paggadde-gadde. This policy is important to ensure the sustainability of the business that supports some of the people with a lowermiddle class economy in Makassar. Keywords: gadde-gadde; restriction; Covid_19; SMEs